Unraveling the genetic and molecular bases of heterosis in a TGMS-based two-line rice hybrid derived F2 segregating population - Azeem, Faraz; Ali, Jauhar; Laude, Tonette. P.; Hosseiniyan Khatibi, Seyed Mahdi; Murugaiyan, Varunseelan; Kumar, Neeraj; Galang, Angelito; Dela Paz, Madonna; De Asis, Erik Jon; Singh, Atul; Robiso, Christian John; Besa, Carla Francesca; et al. (Frontiers in Plant Science, 2026)
IntroductionHeterosis has played a pivotal role in enhancing rice yield, yet its genetic and molecular bases remain only partially understood, particularly in two-line thermosensitive genic male sterile (TGMS) hybrid systems.MethodIn this study, we dissected the genetic architecture underlying heterosis using an F₂ segregating population comprising 392 individuals, derived from the elite TGMS-based hybrid IR144693H (IRAC-43S×IRV932). High-density genotyping was performed using the 1k-Rice Custom Amplicon (1k-RiCA) SNP panel, coupled with comprehensive phenotyping of yield and yield-related traits under field conditions.ResultsQuantitative trait locus (QTL) analysis identified 24 main-effect QTLs associated with seven agronomic and physiological traits, explaining 4.1% to 67.5% of the phenotypic variance. Major-effect QTLs were detected for number of tillers (qNT3011 and qNT6011 on chromosome 11), unfilled grains (qUFG7.2 and qUFG9), and thousand grain weight (qTGW12.1), highlighting key genomic regions contributing to heterosis. The F₂ segregating population exhibited extensive phenotypic variation and transgressive segregation for multiple traits, underscoring the complex and polygenic nature of heterosis in TGMS-based rice hybrid systems.DiscussionIn the absence of system-specific reference genomes and transcriptomic resources for two-line rice hybrids, candidate gene identification was conducted using the Nipponbare reference genome and publicly available expression datasets. Several biologically relevant genes were prioritized within major QTL intervals, including SPP (sucrose-phosphate phosphatase), GW2 (grain width regulator), DEP1 (panicle architecture), and OsCCaMK (calcium/calmodulin-dependent protein kinase), supported by positional evidence and tissue-specific expression patterns.Overall, this study provides a high-resolution dissection of heterosis-associated genomic regions in a TGMS-derived F₂ segregating population and delivers valuable candidate loci for marker-assisted selection and functional validation. These findings advance our understanding of heterosis in two-line hybrid rice and offer practical insights for the development of next-generation high-yielding hybrids.